2018
DOI: 10.21325/jotags.2018.242
|View full text |Cite
|
Sign up to set email alerts
|

Adölesanlarda Kafein Tüketimi (Caffeine Consumption in Adolescents)

Abstract: Adölesan Kafein Tüketim Kafeinli içecekler Kafeinli yiyecekler ÖzKafein son yıllarda özellikle içeceklerde ve bazı yiyeceklerde yaygın olarak kullanılan önemli alkaloitlerdendir. Kafeinin sağlık üzerindeki etkilerine yönelik çok sayıda araştırma olmasına rağmen, özellikle adölesanların kafein tüketimine yönelik yapılan araştırma sayısı oldukça azdır. Bu nedenle bu araştırmada adölesanların kafein tüketimi ve kafein tüketimini etkileyen etmenlerin incelenmesi amaçlanmıştır. Araştırma önemli bir sağlık sorunu ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
(4 reference statements)
0
2
0
Order By: Relevance
“…Consumption of caffeine can cause hypertension. It is very important to evaluate caffeine consumption due to factors such as excessive caffeine consumption that prevent the normal functioning of the central nervous system (Küçükkömürler & Kurt, 2018 ). Caffeinated beverages have gained increasing popularity, especially among young generations, as lifestyles have become more westernized.…”
Section: Introductionmentioning
confidence: 99%
“…Consumption of caffeine can cause hypertension. It is very important to evaluate caffeine consumption due to factors such as excessive caffeine consumption that prevent the normal functioning of the central nervous system (Küçükkömürler & Kurt, 2018 ). Caffeinated beverages have gained increasing popularity, especially among young generations, as lifestyles have become more westernized.…”
Section: Introductionmentioning
confidence: 99%
“…Re-search has revealed that students drink coffee, which has high levels of caffeine, to stay awake and be more active. 9 Although coffee stimulates the central neural system, it may also cause anxiety, poor concentration, exhaustion, addiction, chronic headaches, high blood pressure, depressive psychological mood, and palpitations when large doses are consumed frequently. Coffee also leads to interrupted sleep patterns and may cause children and adolescents to experience memory and learning problems.…”
mentioning
confidence: 99%